An Analysis of EFL Students’ Writing Needs: Considerations for Writing Task-Based Course Design - Do, Hieu Manh (rEFLections, 2023)
The present study adopts the four-step framework of course development processes proposed by Graves (1996) to develop a writing course for EFL Vietnamese undergraduates. A total of 60 students were asked to take a writing test and a survey about writing problems to identify their “objective needs”. Then “subjective needs” were collected from interviews. In addition, the three language teachers were invited to the semi-structured interviews to collect their perspectives on teaching writing, which were analyzed in parallel with students’ needs. The findings show that students’ writing levels are low-intermediate and intermediate, and they have major problems with the organization of ideas, followed by grammar and idea development. Regarding teaching, students’ main concerns are a lack of writing activities and teacher feedback, which may be due to large classes and heavy workloads. To improve students’ writing problems, more writing tasks are needed, including pre-planning (idea development), performance (writing practice), and post-writing (peer feedback, teacher feedback, final draft). These writing tasks are arranged into different phases to help teachers follow up on students’ writing practice and reduce their workloads. Considering these conditions, a proposed writing task-based course was suitable to develop, including the five components of course design: context; goals and objectives; content; method and material; and assessment, as professional support for EFL or ESL language teachers in designing a writing course that can be used for teaching, training, or coaching in a similar context.